O doniosłości rozmowy dydaktycznej w organizowaniu procesu nauczania i uczenia się literatury oraz w badaniu tego procesu = On the significance of the didactic discourse in the organization of the literature teaching/learning process and its research - Biłos, Edward (Zielona Góra: Wyższa Szkoła Pedagogiczna)
There is a necessity of founding the theory of the didactic discourse. The theory is able to throw a new light on presenting both the problems of the organization of the literary education and the problems of researching the process.The present paper bas taken an attempt: l) to define the character of the didactic discourse, 2) to present its structure and function, 3) to present the models of guiding the didactic discourse in teaching/leaining literatura, 4) to present the application of the discourse in researching the process of teaching/learning literatura.
Keywords: dydaktyka literatury; Uczenie się - metody